2017
DOI: 10.7181/acfs.2017.18.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Objective Outcomes of Closed Reduction According to the Type of Nasal Bone Fracture

Abstract: BackgroundNasal fractures have a tendency of resulting in structural or functional complications, and the results can vary according to the type of nasal bone fracture. The aim of this study was to evaluate the objective postoperative results according to the type of nasal bone fractures.MethodsWe reviewed 313 patients who had a closed reduction of nasal bone fracture. The classification of nasal bone fracture by Stranc and Robertson was used to characterize the fracture type: frontal impact group type I (FI),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
1
13
1
Order By: Relevance
“…This study represents one of the largest retrospective reviews on nasal bone fracture and closed nasal reduction outcomes, especially within the United States at a regional level 1 trauma center. 2,6,19,26 Other studies have similarly found assault to be the most common etiology of nasal bone fracture, especially in urban populations. 27,28 Of the patients who underwent CT evaluation, associated facial fractures tended to be in the midface region.…”
Section: Epidemiologymentioning
confidence: 92%
See 3 more Smart Citations
“…This study represents one of the largest retrospective reviews on nasal bone fracture and closed nasal reduction outcomes, especially within the United States at a regional level 1 trauma center. 2,6,19,26 Other studies have similarly found assault to be the most common etiology of nasal bone fracture, especially in urban populations. 27,28 Of the patients who underwent CT evaluation, associated facial fractures tended to be in the midface region.…”
Section: Epidemiologymentioning
confidence: 92%
“…A majority (58.2%) (n = 74) of patients who had CNR followed up in the clinic an average of 11.8 days after the procedure. In follow-up, 19.4% (n = 26) had complaints of nasal obstruction and 14.9% (n = 20) had complaints of nasal deviation. On physical exam, 22.3% (n = 30) had nasal dorsum deviation, and 17.9% (n = 24) had septal deviation.…”
Section: Septal Fracturementioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the type of nasal fracture and the situation in which surgery is being conducted, the surgeon will determine which surgical tools to use [4][5][6][7][8]. Walsham forceps, Asch forceps, and Boies elevators are widely known surgical instruments that are inserted into nasal openings to lift the fracture site for reduction.…”
Section: Introductionmentioning
confidence: 99%